2013
DOI: 10.1108/ijqrm-04-2011-0059
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis between certified and non-certified companies through the quality management system

Abstract: Purpose – The purpose of this study is to analyze a questionnaire answered by a sample of ISO 9000 certified companies and a control sample of companies which have not been certified, using a multivariate predictive model. With this approach, this paper assess which quality practices are associated to the likelihood of the firm being certified. Design/methodology/approach – This paper implemented non-parametric decision trees, in order to see which variables influence more the fact that the company be cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Finally, EP as a CSF for ISO 9001 implementation has been thoroughly studied [80], [83]. Reference [90] claim that both staff management and strategic planning for quality improvement should be prioritized when implementing ISO 9001. In turn, [52] mention that ISO 9001 certified organizations are acknowledged for their highly engaged personnel and their effective approach to fulfilling the standard guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, EP as a CSF for ISO 9001 implementation has been thoroughly studied [80], [83]. Reference [90] claim that both staff management and strategic planning for quality improvement should be prioritized when implementing ISO 9001. In turn, [52] mention that ISO 9001 certified organizations are acknowledged for their highly engaged personnel and their effective approach to fulfilling the standard guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Further, [57] described how top management leadership and the engagement of people provides for the implementation of the standard. In the same matter, [58] showed that the customer focus, human resources management and the strategic planning of the quality should have the highest consideration when implementing the standard. Finally, [59] revealed that the industries certified in the ISO 9001 standard have an excellent relationship management, and, the organization with engaged personnel also, significantly facilitates the accomplishment of the standard guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Total quality management is a management philosophy, transversal to the entire organization, and which incorporates all stakeholders in its model structure, seeking the continuous improvement of organizational performance and customer satisfaction. Several studies that have focused on the role of TQM in competitive advantage have shown that its implementation promotes better performance and greater competitiveness ( Terziovski and Samson, 1999 ; Zhang, 2000 ; Texeira-Quirós and Justino, 2013 ; Texeira-Quirós et al, 2013 ; Antunes et al, 2017 , 2018a ). The application of TQM principles in HEIS has recently emerged, framed in new realities that began to recognize HEIs as profitable organizations ( Antunes et al, 2018a , 2020 , 2021 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many of the researches that have focused on TQM’s repercussions on competitive advantage have shown that their presence leads to improved performance and increased competitiveness ( Terziovski and Samson, 1999 ; Zhang, 2000 ; Texeira-Quirós and Justino, 2013 ; Texeira-Quirós et al, 2013 ; Antunes et al, 2017 , 2018b , 2021 ). In this sense, the following hypotheses of the research were defined:…”
Section: Theoretical Frameworkmentioning
confidence: 99%